FENOMENA KEWARISAN PADA MASYARAKAT BANJAR KALIMANTAN SELATAN - Wahidah Wahidah; Fahmi Al Amruzi (UIN Antasari Banjarmasin, 2022)
The Banjar people are scattered throughout various districts/cities within the South Kalimantan region. In solving inheritance problems, the community seems to use the compromise method by engineering/modifying the farâidh provisions with consideration of a sense of justice, propriety, and benefit. In fact, in many cases, the excesses are not quite reasonable when they are associated with the four phenomenal inheritance variants explored with a qualitative approach. On this basis, the objectives and research problems are formulated in two focus areas: what is the inheritance phenomenon of the Banjar people of South Kalimantan and the meaning behind it? Through in-depth interviews and participant observation of more than 50 informants, data about inherited assets that are not inherited, mandatory wills that have not yet become applied law, grants that bring good fortune to all daughters of the heirs, and delays in the distribution of inheritance. The results of the research here clearly differ from the previous writings because the answers to the research questions are also analyzed using a sociological approach. Two variants of which are still not following farâidh provisions, and the meaning behind the phenomenon of community inheritance is a manifestation or manifestation of the motto